Analysis of CaF2 Precipitation Process in the Selected Static Mixers - Piotr Maria Synowiec; Magdalena Stec (Journal of Chemistry)
In the paper, the analysis of the precipitation process of calcium fluoride in the selected static mixers was made. The Kenics and Koflo static mixers, as well as an empty pipe as a background, have been taken into consideration. The Kenics and Koflo types have been chosen as their inner shapes convenient for the realization of continuous precipitation processes as incrustation phenomenon and dangerousness of flow blocking are not as high as in other solutions. The main tasks were focused on the recognition of the precipitation kinetics (to get the knowledge of the relative supersaturation, nucleation sources, and mechanisms controlling the crystal growth), determination of conversion efficiency of the chemical reaction by which CaF2 is precipitated, the fluid dynamic conditions on crystal size distribution (CSD), and the identification of particles’ destruction sources as well. This paper is a primary work dedicated to the possibilities of a special treatment of the solid phase during its formation in order to obtain the required crystal size distribution (CSD) and to avoid the agglomeration when necessary. The results are very promising. As it will be shown, the special treatment of the precipitated solid substances in static mixers enables to create crystals with the required size and to eliminate the agglomeration phenomenon.